Renewable energy modelling - Bindal Dhruv (2014)
There has been an equivocal and continuing rise in the average temperature of the Earth’s climate over the past few decades. Singapore has already seen rises in sea levels and neighbouring countries have been experiencing intense storms and tropical cyclones. Under such conditions, it has become imperative that alternative sources of energy, which can reduce our carbon footprint, be utilized. Given Singapore’s prominent position in Asia’s Sunbelt, solar energy displays tremendous potential to provide a clean alternative source of energy.